3D Printed Polycaprolactone/Gelatin/Bacterial Cellulose/Hydroxyapatite Composite Scaffold for Bone Tissue Engineering - ŞAHİN, ALİ; OKTAR, FAİK NÜZHET; ŞENGÖR, MUSTAFA; GÜNDÜZ, OĞUZHAN; ÜNAL YILDIRIM, SEMRA (MDPI, 2020)
Three-dimensional (3D) printing application is a promising method for bone tissue engineering. For enhanced bone tissue regeneration, it is essential to have printable composite materials with appealing properties such as construct porous, mechanical strength, thermal properties, controlled degradation rates, and the presence of bioactive materials. In this study, polycaprolactone (PCL), gelatin (GEL), bacterial cellulose (BC), and different hydroxyapatite (HA) concentrations were used to fabricate a novel PCL/GEL/BC/HA composite scaffold using 3D printing method for bone tissue engineering applications. Pore structure, mechanical, thermal, and chemical analyses were evaluated. 3D scaffolds with an ideal pore size (similar to 300 mu m) for use in bone tissue engineering were generated. The addition of both bacterial cellulose (BC) and hydroxyapatite (HA) into PCL/GEL scaffold increased cell proliferation and attachment. PCL/GEL/BC/HA composite scaffolds provide a potential for bone tissue engineering applications.
Keywords: bacterial cellulose; gelatin; polycaprolactone; hydroxyapatite; 3D printing; bone tissue engineering; BACTERIAL CELLULOSE; POLYCAPROLACTONE SCAFFOLDS; GELATIN; FABRICATION; DEPOSITION; FIBERS